2014
DOI: 10.1194/jlr.m045807
|View full text |Cite
|
Sign up to set email alerts
|

Linalool is a PPARα ligand that reduces plasma TG levels and rewires the hepatic transcriptome and plasma metabolome

Abstract: This article is available online at http://www.jlr.org increase in the fasting TG level was associated with 14% and 37% higher incidences of CVD in men and women, respectively ( 3 ). A TG level reduction of the same magnitude could be achieved by dietary interventions, possibly based on the intake of fruits, vegetables, and teas ( 4, 5 ).The ingestion of fragrant herbal teas has been suggested as a simple and effective way of preventing CVD, with green tea being the most widely used ( 6 ). Studies on the hypol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 49 publications
(78 reference statements)
0
19
0
3
Order By: Relevance
“…In mice, linalool reduced plasma TG and saturated fatty acids level and regulated hepatic PPARα target genes. Linalool exhibited similar effects of fenofibrate (Jun et al, ). Some studies have revealed the protective effects of celery extracts on metabolic syndromeas shown in Table .…”
Section: Effects On Hyperlipidemiamentioning
confidence: 80%
See 1 more Smart Citation
“…In mice, linalool reduced plasma TG and saturated fatty acids level and regulated hepatic PPARα target genes. Linalool exhibited similar effects of fenofibrate (Jun et al, ). Some studies have revealed the protective effects of celery extracts on metabolic syndromeas shown in Table .…”
Section: Effects On Hyperlipidemiamentioning
confidence: 80%
“…Moreover, in streptozotocin-induced diabetic rats, the antidiabetic and antihyperlipidemic effects of celery seed extract were studied. Celery seed extract significantly reduced water intake, glucose, cholesterol and TG, alanine aminotransferase, and aspartate amino- (Jun et al, 2014). Some studies have revealed the protective effects of celery extracts on metabolic syndromeas shown in Table 3.…”
Section: Effects On Hyperlipidemiamentioning
confidence: 93%
“…Immunoblotting analysis was used to measure the protein levels of C2C12 and muscle tissues (Jun et al, 2014;Hoang et al, 2015;Jia et al, 2016). Briefly, lysates of skeletal muscle cells and tissues were obtained in a radioimmunoprecipitation assay buffer containing protease and phosphatase inhibitors (Thermo, Waltham, MA, United States).…”
Section: Immunoblotting Analysismentioning
confidence: 99%
“…HEK293 cells also express other receptors implemented in the perception of some of the chemicals tested, e.g. free fatty acid receptor 2 (FFA2) for propionic acid (Brown et al 2003) or peroxisome proliferator-activated receptor (PPAR) α and γ for linalool, citronellol and geraniol (Katsukawa et al 2011, Jun et al 2014. At the moment we cannot conclude if all endogenous responses are mediated by the respective ORs or by an another (olfactory) receptor.…”
Section: Many Odorants Trigger Endogenous Response In Hek293tn Cellsmentioning
confidence: 99%